Supporting Teachers with Telecommunication: The LabNetwork - Richard Ruopp; Meghan Pfister; Brian Drayton; Shahaf Gal (Journal of Research in Rural Education, 1993)
Connected by a computer telecommunication network, ninth-gradersfrom eight high schoolsscattered thousands of miles across Alaska work together, buildingarobotsubmarine togathersamplesfrom the floor ofPrince William Sound. In Colorado, a near-failing student, formerly more interested in her suntan than in science, comes up with an ingenious physics project thatcombines the two: She studies ultraviolet radiation emitted by various types oftanninglamps. In Virginia, twostudents, onesdentifically incli and oneartistic, together explore the mathematical andaesthetic properties ofcertain striking computer graphics. Their topic: IIMandelbrot se s" -,mathematical constructs thatare central to science s new understanding of complex, .chaotic systems, from uieather to thestock market. InArizona,suburban high schoolers design andbuild model cars tomeet strictperformance specifications. They usecomputers todesign prototypes, collect and store data, and write reports. To assess the performance oftheir vehicles, theygenerate detailed graphs of velodty versus time using a sonic measurement device connected to thecomputer